2007
DOI: 10.1590/s0074-02762007005000122
|View full text |Cite
|
Sign up to set email alerts
|

High proportion of hepatitis C virus genotypes 1 and 3 in a large cohort of patients from Southern Brazil

Abstract: Hepatitis C virus (HCV) isolates have been divided into six genotypes (1 to 6). The duration of hepatitis C standard treatment is 48 weeks for patients infected with HCV genotype 1 vs 24 weeks for those infected with genotypes 2 and 3. A total of 1544 HCV isolates from chronic patients living in the southern Brazilian states of Rio Grande do Sul (RS, n = 627) and Santa Catarina (SC, n = 917) were genotyped by restriction fragment length polymorphism (RFLP) of polymerase chain reaction (PCR) products. In RS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
9
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
6
9
1
1
Order By: Relevance
“…This fact can be associated with the study field's proximity to the state of Minas Gerais and the origin of several participants, from this and other states in the Southeast. The occurrence of genotype 3 as the second most frequent is in agreement with findings verified in both Southeast and South Brazil, as well as in the country as a whole (da Silva et al 2007, Botelho et al 2008.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This fact can be associated with the study field's proximity to the state of Minas Gerais and the origin of several participants, from this and other states in the Southeast. The occurrence of genotype 3 as the second most frequent is in agreement with findings verified in both Southeast and South Brazil, as well as in the country as a whole (da Silva et al 2007, Botelho et al 2008.…”
Section: Discussionsupporting
confidence: 89%
“…Genotype 1 represented 80% of the positive samples, a percentage above those described for the states of Rio Grande do Sul, Santa Catarina (da Silva et al 2007) and São Paulo, but similar to that observed in Southeast Brazil (Campioto et al 2005). This fact can be associated with the study field's proximity to the state of Minas Gerais and the origin of several participants, from this and other states in the Southeast.…”
Section: Discussionsupporting
confidence: 75%
“…The bootstrap values > 75% and genetic distance (bar) are indicated. genotype distribution from this study differs substantially from other cohorts of east Argentina as well as in the geographically close region of the South of Brazil, where genotype 1 is predominant (Oubina et al 1995, Picchio et al 2006, Quarleri et al 1998, 2000, da Silva 2007. As far as we know, such high prevalence of subtypes 2c has not been reported previously in any region of South America.…”
contrasting
confidence: 76%
“…These data confirmed that genotypes 1 (53.9%) and 3 (40.7%) were most prevalent in southern Brazil, with frequencies that were similar to those found in the present study. 30 According to the assessment of the geographical distribution of HCV cases, there was higher prevalence of cases in the districts where the populations showed the highest levels of social vulnerability and in a prison where 12 cases (6%) were identified. These districts have low socioeconomic levels and include many places that are used for drug trafficking.…”
mentioning
confidence: 99%